Analisis Performance Web Application Firewall ModSecurity dan Shadow Daemon Dalam Keamanan Web Server Apache - Muhammad Muharromin; Suryayusra (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
The application of a security system on the web needs to be done considering that the web itself can be accessed through a public network. In this research, it will be applied and analyzed the security performance based on the Web Application Firewall using ModSecurity and Shadow Daemon, where the purpose of implementing this web security system is to understand the concept of a security system on the web, performance and pay attention to the results before the application of the firewall and after the application of the firewall on the web. . This study uses the Action Research method, in this study data collection and implementation of a web application firewall using ModSecurity and Shadow Daemon as a web security system is carried out, then an analysis is carried out to get the right recommendations and for a firewall as a web security system. The results of this study indicate that a firewall using Modsecurity and Shadow Daemon-based Web Application Firewall on a web security system can block SQL Injection, Cross Site Scripting (XSS), by displaying an error message to the user who performs the command.